PENGARUH CYBERBULLYING TERHADAP KESEHATAN MENTAL PADA REMAJA - Jessica Wulandari; Nadjwa Khairunnisa; Siti Yolandari; Tanjung Maulio Ar'Roufu; Robby Subagja (Universitas Islam Kalimantan Muhammad Arsyad Al-Banjari Banjarmasin, 2024)
In the current digital era, social media has become an integral part of teenagers lives. However, excessive and uncontrolled use of social media can have negative impacts on teenagers mental heath. The use of social media can also lead to violence among teenagers, one of which is cyberbullying. Teenagers often do not realize that they do cyberbullying, which can have serious effects on the mental health of the victims. This research uses qualitative methods with literature studies. The primary source used is previous research related to this research. The results of the research show that teenage girls tend to be victims of cyberbullying while teenage boys tend to be perpetrators of cyberbullying. Teenagers who experience cyberbullying often feel anxiety, depression, fear, feelings of terror, anxiety, suffering, sadness and stress.